Pengaruh Jarak Tanam dan Jumlah Bibit Per Lubang Terhadap Pertumbuhan Padi Lokal Sumbawa (Oryza sativa L.) - Lestari Lestari; Wening Kusumawardani; Heri Kusnayadi (Indonesian, 2021)
The aim of this study, was to determine the effect of spacing and number of seeds per planting hole on the vegetative phase of local Sumbawa rice plants in paddy fields. This research was conducted for 3 months. This study, used quantitative method with factorial randomized block design (RBD) with 2 factors, namely are the use of spacing (J) and the number of seeds per planting hole. Each treatment was repeated 3 times. The factor of using spacing consists of 2 levels and the factor of number of seeds per planting hole consists of 3 levels. The results of the analysis showed that the combination treatment had an effect on the spacing and number of seeds per planting hole had a significant effect on the parameter of the number of tillers. The single factor of spacing has a significant effect on the parameter of the number of tillers. The single factor of the number of seedlings per planting hole had a significant effect on the parameter of the number of tillers.